Currency Fluctuations and the Perception of Corporate Performance (Book). - Parker, Lee D.; Brief, Richard P. (The Accounting Review, 1987)
Abstract Reviews the book "Currency Fluctuations and the Perception of Corporate Performance," by Loretta Graziano.